Wave Interactions with Coastal Structures - Suzuki, Tomohiro; Altomare, Corrado (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Due to the ongoing rise in sea level and increases in extreme wave climates, which consequently change the wave climate, coastal structures such as sea dikes and seawalls are exposed to severe and frequent sea storms. Even though much research related to wave-structure interactions has been carried out, it remains one of the most important and challenging topics in the field of coastal engineering. The recent publications in the Special Issue "Wave Interactions with Coastal Structures" in the Journal of Marine Science and Engineering include a wide range of research, including theoretical/mathematical, experimental, and numerical work related to the interaction between sea waves and coastal structures. These publications address conventional coastal hard structures in deep water zones as well as those located in shallow water zones, such as wave overtopping over shallow foreshores with apartment buildings on dikes. The research findings presented help to improve our knowledge of hydrodynamic processes, and the new approaches and developments presented here will be good benchmarks for future work.